2015
DOI: 10.3390/su71114558
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Public Bicycle Adoption Using the Technology Acceptance Model

Abstract: Abstract:Bicycle sharing programs provide a sustainable mode of urban transportation. Although cities across the globe have developed these systems for their citizens and visitors, usage rates are not as high as anticipated. This research uses the technology acceptance model as the basis to understand one's intention to adopt bicycle sharing programs. Using survey data derived from 421 participants in Beijing, China, the proposed covariance-based structural equation model consisting of perceived quality, perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 49 publications
1
37
0
1
Order By: Relevance
“…For example, [49] adopted an extended technology acceptance model (TAM) and found that customer's attitude toward the smart bike-sharing systems and perceived usefulness positively affect their use intention. [41] also discovered that perceived quality (perceived usefulness) and perceived convenience Page 647 (perceived ease of use) foster the adoption of public bicycle sharing systems through perceived value.…”
Section: Technology Acceptance Model (Tam) and Theory Of Planned Behamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [49] adopted an extended technology acceptance model (TAM) and found that customer's attitude toward the smart bike-sharing systems and perceived usefulness positively affect their use intention. [41] also discovered that perceived quality (perceived usefulness) and perceived convenience Page 647 (perceived ease of use) foster the adoption of public bicycle sharing systems through perceived value.…”
Section: Technology Acceptance Model (Tam) and Theory Of Planned Behamentioning
confidence: 99%
“…Within the limited studies of the intention to use bike-sharing systems, some researchers borrowed the technology acceptance model (TAM) [25] to examine the effects of two system features (i.e., perceived usefulness (PU) and perceived ease of use (PEOU)) on users' adoption of bike-sharing systems [41,49]. Apart from that, other scholars adopted the theory of planned behavior (TPB) [5] to examine the influence of users' attitude, subjective norms and perceived behavioral control on their intention to use bikesharing systems [46].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, overall energy consumption and GHG emission levels in the transportation sector are likely to rise further. This increase is in spite of the fact that-besides the quantitative numbers-the societal and corporate acceptance of the overall sustainability concept for logistics is assumed to be a given, though major concerns for e.g., customer acceptance [23,24], reach (i.e., for governmental as well as non-governmental non-profit organizations, see [25,26]), as well as control and monitoring [15,27,28] resume. Still, the described research question of why the concept of green and sustainable logistics failed in general, especially regarding emissions impact, remains open; but before diving deeper into it we must take a look in Section 3 at the technology development, which for many actors is the main source of hope for successful green logistics.…”
Section: History and Status Quomentioning
confidence: 99%
“…The objective of green logistics in terms of reduced energy consumption as well as emissions has not been successful within the European Union (EU-28); the share of greenhouse gas (GHG) emissions caused by the transportation and logistics sector has risen from 16.6% in 1990 to 24.3% in 2012 [17]. In total absolute emissions, this means an increase from 962.6 to 1173.3 million tons of CO 2 equivalents per annum (in itself an increase of 21.89%, or roughly 1% per year) as outlined in Table 1.…”
Section: History and Status Quomentioning
confidence: 99%
“…Dell et al indicated that the major problem concerning the operator in a BSS is to redistribute bicycles quickly during rush hour [5]. If the operator cannot avoid the system imbalance (it is hard to park at some stations, while other stations have no bicycles available to rent), the satisfaction of users declines and users may even abandon this new mode of transport action [6,7].…”
Section: Introductionmentioning
confidence: 99%